Comparing CALL and VAL-ED: An Illustrative Application of a Decision Matrix for Leadership Feedback Instruments. Issue 1 (January 2019) - Salisbury, Jason; Goff, Peter; Blitz, Mark
Initiatives to increase leadership accountability coupled with efforts to promote data-driven leadership have led to widespread adoption of instruments to assess school leaders. In this article, we present a decision matrix that practitioners and researchers can use to facilitate instrument selection. Our decision matrix focuses on the psychometric properties of the instruments, the model of leadership used to construct the instruments, the feasibility of implementation, and the extent to which feedback lends itself to changes in behavior (actionability). We apply this decision matrix to two of the most prominent leadership feedback instruments, Comprehensive Assessment of Leadership for Learning and Vanderbilt Assessment of Leadership in Education. Through our decision matrix, we are able to reveal the commonalities between the measures and also identify tangible differences. We discuss the implications of the comparative strengths and drawbacks of the two instruments and how they might be deployed most effectively to improve leadership practices.